Loan Repayment Behaviour Among the Rubber Farmers in Nesi Project in East Aceh, Indonesia - Azhar, (1999)
As an effort to promote the national rubber industry, the government of Indonesia in the past has implemented various policies and programmes. One of them is the Nucleus Estate and Smallholders I Project (NES). The NES I project was officially introduced in 1977 as a pilot project in implementing the contract farming system in Indonesia, and it has progressively developed ever since. It involved a total area of about 5,852 hectares and 2,926 farmers. However, the project faced one major problem, that is poor loan collection where quite a Significant number of farmers involved in the project who were not able to repay the loan on time. According to the Pusat Pengkajian dan Pengembangan Agribisnis (1994), the total amount of loans that had been disbursed by the NES project was RP 12.690 billion and out of this amount only R P 6.533 billion or about 51 percent had been repaid by the project participants.Recognition the above problem, the general objective of the study is to examine the loan repayment performance of a contract farming system through the NES I Project in East Aceh, Indonesia. The specific objectives of the study are to assess the performance of the non-defaulters and the defaulters in terms of their productivity, income and adoption of technology; and to identify key factors influencing borrowers of NES I project to repay their loans. This study was conducted at the NES I project, which is located at about 89 km from Langsa in East Aceh District of Aceh Province, Indonesia, and adjacent to the State-Owned Enterprise, i.e., PT. Perkebunan Nusantara I. For the purpose of this study, one hundred respondents were chosen as the sample of the study which consisted of 65 non-defaulters and 35 defaulters. The study shows that, with the exception of the tapping frequency, there is no significant difference between the non-defaulters and the defaulters in terms of some of the economic variables such as level of productivity, income level and adoption of technology. The analysis of logit model which provides 81 percent of correct prediction indicates that, with the exception of the farmers' income level, the signs of the estimated coefficients of other explanatory variables are as expected according to a priori reasoning. Generally, the model indicates that the probability that a farmer will become a non-defaulter is positively related to educational attainment, farming experience, productivity, other sources of income, attitude towards loan repayment, knowledge about the rubber technology and satisfaction with the NES I project activities and services, but negatively related to age, family size and income. However, only the coefficients of educational attainment, family size and knowledge about the rubber technology are found to be significant at the 5 percent level.